A Legal Protection Model for the Resolution of Child Labor Disputes in Companies under Indonesian Employment Law - Siti Nurhayati; Rika Jamin Marbun (Journal of Law, Politic and Humanities, 2026)
Child laborers are a vulnerable group facing risks of economic exploitation, excessive working hours, inadequate wages, workplace accidents, unilateral termination of employment, and disruption of their rights to education and healthy growth and development. This study aims to analyze legal protections for child laborers in companies and to formulate a dispute resolution model oriented toward the best interests of the child. The study employs a normative legal method using both a statutory and a conceptual approach. Primary legal sources include labor regulations, child protection laws, industrial relations dispute resolution provisions, international conventions, Constitutional Court rulings, and labor inspection regulations. The research findings indicate that the Labor Law, in principle, prohibits companies from employing children but provides limited exceptions for light work, work for educational or training purposes, and work intended to develop talents and interests. Resolving child labor disputes is insufficient if it relies solely on industrial relations dispute mechanisms, as some cases may involve elements of exploitation, violence, child trafficking, or hazardous work. This study proposes an Integrated Legal Protection Model for Child Labor consisting of four layers: prevention and corporate compliance; child-friendly complaint handling; resolution through dual channels of labor and child protection; and recovery and ongoing monitoring. This model treats the fulfillment of children’s rights, the cessation of hazardous work, the payment of labor entitlements, educational rehabilitation, and law enforcement as a single, integrated process.